Estimating The Necessity For Brake Spare Parts at PT XYZ Using The Monte Carlo Method - NUR HIDAYAH NINGSIH, Nur Hidayah Ningsih; Mufti Arifin; Muhammad Hadi Widanto (Jurnal Teknologi Kedirgantaraan, 2025)
Brake is a crucial component of an aircraft. The availability of brake parts is a challenge for the company, affecting operational performance and customer satisfaction. The analysis at PT XYZ aims to predict the need for brake parts using historical replacement data and Monte Carlo Models. Brake replacement data is random because it is not known when it should be replaced. The results showed that brake replacement in 2022 and 2023 was 886. By using linear regression, the estimated need for brake spare parts in 2024 is 258,4301 for 117 aircraft with three types used A320, B737-900ER, and B737-9 MAX. The number of brake replacements for 2 years is 886 while the Monte Carlo simulation results amount to 922. Comparison of Airlines obtained prediction results, ABC is 389, BCD is 425 and CDE is 135. Part Number comparison obtained predictions, 2-1740-1 is 479, C20225510 is 318, and C20633000 is 160. Comparison for 6 months in 2024 obtained a difference of 7%. Comparison of Airlines obtained a difference of ABC is 17%, BCD is 25%, and CDE is 7%. While the Part Number Comparison obtained a difference of 2-1740-1 is 32%, C20225510 is 12%, and C20633000 is 2%.